The Effect of Structured Educational Intervention Using Animated Videos on Stunting Prevention Knowledge Among Mothers of Children Under Five - Debrina Viola Safitri; Eny Sendra; Koekoeh Hardjito; Ririn Indriani (Oksitosin : Jurnal Ilmiah Kebidanan, 2026)
Stunting caused by chronic malnutrition remains a major public health problem among children under five in Indonesia. Improving mothers' knowledge through health education is considered an important strategy for supporting stunting prevention. This study aimed to assess changes in mothers' knowledge of stunting prevention following a structured educational intervention using animated videos in Bujel Village, Kediri City. A pre-experimental study employing a one-group pretest-posttest design was conducted among 44 mothers of children aged 12–59 months selected through simple random sampling from a population of 301 mothers. The intervention consisted of two approximately five-minute structured educational sessions using animated videos on child nutrition and stunting prevention. Mothers completed the same knowledge questionnaire before and immediately after the intervention. Data were analyzed using the Wilcoxon Signed-Rank Test. The proportion of mothers with good knowledge increased from 68.2% before the intervention to 88.6% afterward. The improvement in knowledge was statistically significant (p = 0.015). These findings indicate that a structured educational intervention using animated videos was associated with improved maternal knowledge of stunting prevention. However, because this study employed a one-group pretest-posttest design without a control group, the findings should be interpreted as evidence of improved knowledge following the intervention rather than definitive proof of intervention effectiveness.